Penanaman Karakter Anak Pedesaan Melalui Kajian Dan Seni Al-Quran: Perjalanan Mahasiswa KKN Di Desa Tanjung Dalam - Asti Haryati; Muhammad Farhan Mahesa; Nungki Nungki; Meranti Injelia; Ersa Enzelita; Selfi Sintia; Junita Anggun Rosalinda; Destri Putri; Novia Mahlia Sari; Muhammad Andri; Edwin Ansori (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
This article reviews the experience of students from KKN Group 10 of UINFAS Bengkulu in instilling character in children in Tanjung Dalam Village through Quranic studies, learning Arabic through songs, and writing and coloring calligraphy. This program is designed to enhance academic skills while fostering religious, creative, and cultural character in children using developmental methods and the ABC (Activity-Based Curriculum) Method. The results show significant improvements in children's participation, teaching quality, academic skills, and creativity. Support from parents and the community also played a crucial role in the program's success. This program is expected to serve as a model for other villages to adopt in order to instill character in children through engaging and educational activities.